ТАЛАБАЛАРДЫҢ КӨРКЕМ-ДӨРЕТИЎШИЛИК УҚЫПЛЫЛЫҚЛАРЫ МЕНЕН ЭСТЕТИКАЛЫҚ ТАЛҒАМЫН СҮЎРЕТЛЕЎ ӨНЕРИ ЖӘРДЕМИНДЕ РАЎАЖЛАНДЫРЫЎДЫҢ ТИЙКАРЛАРЫ - Уразимова, Т.В. (SCIENCE and SOCIETY, 2025)
The article is devoted to the development of artistic and creative abilities and aesthetic taste in students. Considering the development of artistic and creative abilities of students and aesthetic taste in the context of the history of the formation and development of fine and decorative and applied arts, we take into account the process of influence of aesthetics on the formation of personality. In this regard, we pay attention to aesthetics as a theory of aesthetic education, aesthetic pedagogy, as a significant component influencing the development of artistic and creative abilities of students in the process of teaching fine and decorative and applied arts.
Keywords: artistic and creative abilities; aesthetic taste; fine arts; pedagogy